Analisis Faktor-Faktor yang Mempengaruhi Auditor Switching (Pada Perusahaan Manufaktur yang Terdaftar pada BEI Periode 2011-2015) - , Mariyatun, Dr. Triyono, S.E., M.Si (2017)
The objective of this research is to know influence of changing of management, financial distress, percentage change of ROA, company size measure to auditor switching. This research used quantitative method by using data of secondary seen manufacturing business annual report which enlist in Indonesia Stock Exchange (BEI). Population in this research is manufacturing business which enlists in Indonesia Stock Exchange (BEI) during period 2011-2015. Method gathering of sample use method of purposive sampling. The analyses which used logistic regression. Reason of usage of analyzer of logistic regression because variable of dependent have the character of dichotomy doing auditor switching and do not to do auditor switching. Result of research indicated that changing of management have an effect on to expression auditor switching. Distress Financial do not have an effect on to auditor switching. Percentage changes of ROA do not have an effect on to auditor switching. Company size measures have an effect on to auditor switching.